2023
DOI: 10.48550/arxiv.2303.10326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diff-UNet: A Diffusion Embedded Network for Volumetric Segmentation

Abstract: In recent years, Denoising Diffusion Models have demonstrated remarkable success in generating semantically valuable pixel-wise representations for image generative modeling. In this study, we propose a novel end-to-end framework, called Diff-UNet, for medical volumetric segmentation. Our approach integrates the diffusion model into a standard U-shaped architecture to extract semantic information from the input volume effectively, resulting in excellent pixel-level representations for medical volumetric segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This study has several limitations. The Diffusion Probabilistic Models (DPMs) [ [45] , [46] , [47] , [48] ] have recently shown outstanding performance in the field of medical image segmentation. By simulating the diffusion process between image voxels, DPMs refine image features and capture contextual information, allowing them to implicitly recognize complex patterns and subtle changes within images.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations. The Diffusion Probabilistic Models (DPMs) [ [45] , [46] , [47] , [48] ] have recently shown outstanding performance in the field of medical image segmentation. By simulating the diffusion process between image voxels, DPMs refine image features and capture contextual information, allowing them to implicitly recognize complex patterns and subtle changes within images.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the performance of MedSegDiff, Wu et al 35 proposed a conditional Transformer network framework and a SS-Former module to model the information interaction between the semantic features and Gaussian noise. Xing et al 38 proposed a medical volumetric image segmentation method, called Diff-UNet, which introduces the DDPM into the U-Net model to provide excellent pixel-level representation.…”
Section: Generative Model-based Medical Image Segmentationmentioning
confidence: 99%
“…However, for 3D volumetric data such as MRI images, using 2D image slices will lose some of the spatial information. In addition, some diffusion models 34,38 based on U-Net are often unable to capture remote dependencies and extract global spatial feature information from MRI images. To address the above challenges, we design an algorithm based on diffusion model to achieve accurate brain tumor segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Although SAM can be applied to each slice of a volume to get the final segmentation, it does not consider the correlation in the depth dimension. Many previous studies have shown that depth correlation is essential for 3D medical image segmentation [14,15,39]. To address this issue, we propose a novel adaptation method inspired by the image-to-video adaptation, with some modifications.…”
Section: Msa Architecturementioning
confidence: 99%